ID 31 – Impact of magnetoencephalography on the decision made by the Danish multidisciplinary epilepsy surgery team. Issue 3 (March 2016) - Duez, L.; Beniczky, S.; Tankisi, H.; Sabers, A.; Sidenius, P.; Fuglsang-Frederiksen, A.
Abstract : Objective: This prospective ongoing study investigates the impact of magnetoencephalography (MEG), as a non-invasive tool to guide the multidisciplinary epilepsy surgery team. Methods: MEG (306 channels) was recorded in 18 patients with refractory focal epilepsy, referred for epilepsy surgery. All patients underwent conventional non-invasive presurgical evaluation. The Danish epilepsy surgery team evaluated the patients blinded and two weeks later unblinded to MEG. At both sessions the multidisciplinary team determined the localisation of the epileptogenic zone and decided on surgical or additional presurgical plans. The impact of MEG was divided into eight predefined categories: No change, change from operation not possible to implantation of intracranial electrodes, change form operation not possible to operation, change from implantation to operation, change from operation to implantation, change from operation to stop, change from implantation to stop, and change of implantation strategy. Results: Three patients changed from operation not possible to operation. One patient changed from operation not possible to implantation. In two patients the implantation strategy changed. In the remaining 12 patients MEG had no impact. Conclusion: MEG makes epilepsy surgery possible in patients where conventional non-invasive presurgical evaluation did not localize the epileptogenic zone. Key message: MEG can change the decision of the epilepsy surgery team.